Peran Dukungan Sosial Keluarga dan Kemandirian Belajar terhadap Flourishing pada Mahasiswa yang Terancam Drop Out - Ridha, A. Ahmad (UIN Sunan Kalijaga, 2022)
Flourishing is the highest level of human psychological well-being. Flourish conditions are needed by students who nearly drop out in completing their education at college. This study aims to determine the role of family social support in the flourishing of students who nearly drop out, moderated by independent learning. This study uses a quantitative approach at university X in Tarakan, North Kalimantan. The subjects of this study were 70 students who nearly dropped out. The results of the moderated regression analysis show that family social support and independent learning play a positive role in student flourishing. However, learning independence still needs to be proven to strengthen the role of family social support for flourishing students who nearly drop out. This means that independent learning does not have a significant moderating effect as a moderating variable. Flourishing merupakan tingkatan tertinggi dari kesejahteraan psikologis manusia. Kondisi flourish sangat dibutuhkan mahasiswa yang terancam drop out dalam menyelesaikan pendidikannya di institusi pendidikan. Penelitian ini bertujuan untuk mengetahui peranan dukungan sosial keluarga terhadap flourishing mahasiswa yang terancam drop out yang dimoderatori oleh kemandirian belajar. Penelitian ini menggunakan pendekatan kuantitatif di Universitas X di kota Tarakan, Kalimantan utara. Subjek penelitian ini adalah 70 orang mahasiswa yang terancam drop out. Hasil moderated regression analysis menunjukkan bahwa dukungan sosial keluarga dan kemandirian belajar secara bersama-sama berperan positif terhadap flourishing mahasiswa, namun kemandirian belajar tidak terbukti memperkuat peranan dukungan sosial keluarga terhadap flourishing mahasiswa yang terancam drop out. Ini berarti bahwa kemandirian belajar tidak memiliki efek moderator yang signifikan sebagai variabel moderator